2001
DOI: 10.1118/1.1339227
|View full text |Cite
|
Sign up to set email alerts
|

Optimal detection of the neutron capture therapy agent borocaptate sodium (BSH): A comparison between 1H and 10B NMR

Abstract: Boron Neutron Capture Therapy (BNCT), an experimental binary cancer treatment modality, requires selective targeting of 10B containing compounds to tumors. One of the compounds under evaluation in an EORTC phase I trial, and used in Japan for patient treatments for many years, is borocaptate sodium (BSH, also known as sulfhydril boron hydride). To optimize the clinical applications, a noninvasive method is needed to monitor the distribution of the boron compound, and NMR may offer such a possibility. A compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…44 A theoretical and practical evaluation of the relative merits of 10 B and 1 H NMR for the detection of BSH in-vivo was conducted. 40 The results of that study showed that the sensitivity advantage of 1 H detection is not as obvious as intuitively assumed. Fundamental considerations, based on the spin quantum number I and the gyromagnetic ratio , predict an enhancement factor of 28.9 in favor of 1 H in the limit of noise dominated by coil resistance (which applies to small non-conducting samples), but when the noise is dominated by the sample itself, this enhancement factor is reduced to 5.4.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…44 A theoretical and practical evaluation of the relative merits of 10 B and 1 H NMR for the detection of BSH in-vivo was conducted. 40 The results of that study showed that the sensitivity advantage of 1 H detection is not as obvious as intuitively assumed. Fundamental considerations, based on the spin quantum number I and the gyromagnetic ratio , predict an enhancement factor of 28.9 in favor of 1 H in the limit of noise dominated by coil resistance (which applies to small non-conducting samples), but when the noise is dominated by the sample itself, this enhancement factor is reduced to 5.4.…”
mentioning
confidence: 83%
“…Thus, the apparent transverse relaxation rate is slower than that of 11 B under the same circumstances, which was also corroborated by theoretical simulation. 40 Each molecule of BSH has 11 hydrogen atoms which are directly attached to boron, and in the case of 10 B, the scalar coupling constant is J ¼ 43 Hz. Therefore, it seems reasonable to somehow benefit from this interaction for the detection of 10 B-enriched BSH molecules, which was first proposed by De Luca et al 41 The most sensitive realization of this concept should involve a pulse sequence, in which the proton magnetization is excited and detected after a 10 B-editing filter, which passes only the signal from hydrogens coupled to 10 B.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the in vivo MR imaging of BSH was demonstrated only for the natural abundance compound (5), using 11 B detection ( 11 B has 80% natural abundance). This approach is obviously not suitable for clinical applications, where the boronated molecules are enriched in 10 B to over 95%. It was always assumed that direct 10 B detection would not be sensitive enough for MRI of BNCT agents, due to the low gyromagnetic ratio of 10 B, and therefore considerable efforts were devoted to the development and implementation of indirect detection methods.…”
mentioning
confidence: 99%
“…Boron neutron capture therapy (BNCT) is based on the high cross section of 10 B for capturing thermal neutrons (1,2). This nuclear reaction yields alpha particles and recoiling lithium nuclei, both with high linear energy transfer (LET) and relatively short spatial range (ϳ10 m).…”
mentioning
confidence: 99%